Peningkatan Aktivitas Belajar IPS melalui Penerapan Strategi “Romusha” pada Siswa Kelas V SD I Wolowona II Ende - Anselmus Mema (Journal on Education, 2023)
The purpose of this classroom action research was to increase social studies subject learning activities for fifth grade students at SDI Wolowona II Ende Regency by using the 'Romusha' strategy. This classroom action research was carried out at SDI Wolowona II in class V with a total of 28 students. This classroom action research was carried out using two cycles, cycle 1 consisting of three meetings and cycle 2 consisting of 2 meetings. The data in this study are in the form of teacher activities, student learning activities, and student responses in teaching and learning activities. Collecting data in this study using observation/observation, questionnaires, interviews, and documentation. The learning activities carried out by the teacher can be formulated as follows: Learning planning, there is an increase from 85% in cycle I to 95% in cycle II. While the implementation of learning carried out by the teacher also increased from 79.17% in cycle I to 87.50% in cycle II. Student learning activities have increased, in the first cycle of 64.84%, to 82.14%, in the second cycle. Meanwhile, students' responses to teaching and learning activities can be described as follows: qualifications that express displeasure no longer exist, both in cycle I and in cycle II. Meanwhile, those who stated that their qualifications were not happy showed a decrease from 13 students (32.5%) in cycle I to 5 students (12.5%) in cycle II. Qualifications that said they were happy experienced an increase from 16 students (55%) in cycle I to 26 students (65%) in cycle II. Qualifications that said they were very happy experienced an increase from 5 students (12.5%) in cycle I to 9 students (22.5%) in cycle II.